UNDERSTANDING THE NATURE OF TRANSLATION TOOL - Condro Nur Alim (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2011)
The emergence of Machine Translation, known as MT has given a new hope to abridge the problems in translation. Ideally, it is designed to create a fully automatic high quality translation (FAHQT). People do hope that a bulk number of work deals with translating a text from source language to target language can be done easily and accurately. Further, it is believed that machine translation will be cheaper compared to ‘human translation’. The question is does this machine really translate a text well? Unfortunately, many facts show that machine translation produces an unsatisfying translation result. The main factor underlying this fact is that this machine failed to abridge linguistics complexity, which is characterized as context dependent, although it has been designed in such a way to overcome that linguistics complexity. Meanwhile, under the right circumstances, many believed that MT systems are a powerful tool. This paper focuses on the nature of machine translation and the possibility in empowering it. After recognizing the nature of machine translation, it is hoped that the users of the machine can take any appropriate actions to make the benefit of machine translation.